QOLP-18. A TIME-BASED MODEL OF EARLY PALLIATIVE CARE INTERVENTION IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA, A SINGLE INSTITUTION FEASIBILITY STUDY. (11th November 2019) - Johnson, Margaret; Ramirez, Luis; Herndon, James; Massey, Woody; Lipp, Eric; Affronti, Mary; Kim, Jung-Young; Friedman, Henry; Desjardins, Annick; Randazzo, Dina; Ashley, David; Casarett, David; et al.
Abstract: OBJECTIVE: There is no validated model for delivering palliative care (PC) in the glioblastoma (GBM) population. The primary objectives were to assess the feasibility and determine the acceptability of a time-based model of integrated specialty PC to patients and providers. Secondary objectives were to estimate the impact on healthcare utilization and quality of life (QoL) compared to historical controls. METHODS: We consented and referred patients to PC at their initial Neuro-Oncology consultation between 4/2018 and 5/2019. We conducted QoL assessments (NCCN Distress Tool; Functional Assessment of Cancer Therapy-Brain (FACT-BR); Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F); Epworth Sleepiness Scale (ESS)) at (1) baseline (2) immediately after chemoradiation, and (3) 6 months following chemoradiation. Ongoing PC follow-up was at the discretion of the PC provider. We administered the Edmonton Symptom Assessment System (ESAS) before and after PC visits. We measured patient and referring provider satisfaction using FAMCARE-16 and a PC departmental survey, respectively. RESULTS: We did not meet our goal enrollment of 50 patients. 32 were offered participation, 12 consented and 8 attended at least one PC visit. The mean number of PC visits was 1.6. Mean age was 62 (42–79). 75% had a KPS ≥80. Of those that did not complete the study, 2 died and 5 either withdrew consent or declined further visits. At baseline, 91.7 % had a NCCN distress score ≥4. Patients were overall satisfied with the intervention. CONCLUSION: Introduction of specialty PC at the time of GBM diagnosis is challenging. Participants reported their experience as overall positive. Results from referring providers are pending. Due to low-enrollment we did not pursue further statistical comparisons regarding healthcare utilization compared to historical controls.